"THE PROBLEMS OF TRANSLATING FIGURATIVE LANGUAGE: EXAMINING 'THE SNIPER'" (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explores the challenges and intricacies involved in translating figurative language from Liam O'Flaherty's short story "The Sniper" into Uzbek, undertaken by translator Feruz Ziyofullaev. Figurative language, encompassing metaphors, similes, hyperboles, and personification, enriches literary texts by adding depth, emotion, and vivid imagery. However, translating these elements across languages poses significant difficulties due to cultural and linguistic differences. Through a comparative analysis of specific examples from the original English text and its Uzbek translation, the study reveals how some figurative expressions are preserved, while others are altered or lost. The findings highlight the impact of these changes on the overall tone, emotional resonance, and stylistic quality of the translated work. The article underscores the importance of a nuanced approach to translation, emphasizing the need for creative adaptation to maintain the expressive power of the original text. This article examines the challenges involved in translating figurative language, specifically addressing how figurative expressions are rendered across different languages and cultural contexts.